The relationship between the interest and competency of driving teachers on the graduation rate in the driving teacher program in Riau Province - Nendra, Robby Celvin; Darmansyah, Darmansyah; Eldarni, Eldarni; Amsal, Mutiara Felicita (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The Teacher Mobilization Program (PGP) is one of the strategic initiatives of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia to produce learning leaders who are able to create a quality learning environment. However, in Riau Province, the graduation rate for participants in this program shows significant variations between different classes. This research aims to analyze the relationship between the interests and competencies of Driving Teachers and their graduation rates in the Driving Teacher Program in Riau Province. This research uses a quantitative approach with a correlational design. Data was obtained through a questionnaire distributed to PGP participants from class 9 to class 11 in Riau Province. The data analysis technique uses the Pearson correlation test and multiple linear regression to measure the influence of interest and competency on graduation rates. The research results show that both interest and competency have a significant relationship with graduation rates. Teachers with high interest and competence have a greater opportunity to complete the program with optimal results. Simultaneously, the combination of interest and competence showed a greater influence on participant success than each factor individually. These findings can be used as a reference for policy makers in designing strategies to increase the readiness and competence of PGP participants in the future.